Genetic footprints of Quaternary glacial cycles over the patterns of population diversity and structure in three Nacella (Patellogastropoda: Nacellidae) species across the Magellan province in southern South America - González-Wevar, Claudio A.; de Aranzamendi, María Carla; Segovia, Nicolás I.; Rosenfeld, Sebastián; Maturana, Claudia S.; Molina, Cristian Ríos; Brickle, Paul; Gardenal, Cristina N.; Bastida, Ricardo; Poulin, Elie (Frontiers in Marine Science, 2023)
Quaternary glaciations severely altered landscape/seascape at high latitudes and had major consequences on species geographical ranges, population sizes, genetic differentiation and speciation rates. The Magellan province in southern South America, constitutes an interesting area to evaluate the effect of glaciations over near-shore marine benthic organisms. Existing data have showed clear signatures of population genetic bottlenecks during glacial maxima followed by recent recolonizations and expansions during the interglacial. Here, we present new population-based analyses in species of the patellogastropod genus Nacella (N. deaurata, N. magellanica, and N. mytilina). The species N. magellanica and N. deaurata inhabit rocky ecosystems while N. mytilina lives closely associated with kelps. The analyzed species exhibit narrow bathymetric ranges and consequently should have been severely affected by recurrent glacial cycles. We performed phylogeographic and demographic analyses in Nacella species including different localities across their respective distributions in the Magellan province including the Falkland/Malvinas Islands (F/M). Genetic analyses showed that all Nacella species exhibited low levels of genetic diversity, the presence of single dominant broadly distributed haplotypes, lack of correlation between geographical and genetic distance, and recent demographic growths, which are evidence supporting rapid postglacial expansions. Such results may have been facilitated by larval and/or rafting-mediated dispersal following the Cape Horn Current System. The three species showed strong and significant differentiation between F/M and southern Pacific margin (SPM) populations including localities across the Strait of Magellan and Cape Horn. Haplotype genealogies and mismatch analyses recognized older and more complex demographic histories in the F/M than in South America. Different glaciological histories between SPM and F/M may be responsible of the marked phylogeographic structure in the analyzed species of Nacella. Alternatively, as previously proposed, the F/M represent a glacial refugium for Nacella species (sink area), as well as a secondary contact zone where endemic haplotypes are found together with recently arrived South American ones. Historical and contemporary processes, contrasting glacial histories between the analyzed areas, as well as life history traits of the analyzed organisms are main factors explaining current phylogeographic patterns of shallow Magellan marine benthic organisms.